PEMBANTU DAN PELACUR: SEBUAH TINJAUAN BUDAYA - Hiqma Nur Agustina (Universitas 17 Agustus 1945 Surabaya, 2016)
Abstract. The development of popular literary works in Indonesia today is increasingly widespread. Many talented young writers are writing their brilliant and surprising themes, characters and storyline in their writings. One of the short stories entitled â€œPembantu dan Pelacurâ€ written by Roidah. This paper aims to explore the meaning of a text of short story using semiotic theory and cultural studies. Women's issue raised in this text is often happened in our environment, trapped in the black world for being victims of violence and then plunged in a professional manner because they do not have a choice. Some of the concepts used to study the text, namely: structure, systems, relationships, representation and significance. The conclusion of this paper is that there is a class structure and social system that consists of strata layers of the lower class, middle class and upper class which is connected one to another. The social relation that appear in the form of a Barbie doll that represents the ideal female figure from different strata of society is being arisen in the story. Its significance can be seen in this text as a respectable figure of a woman who is able to keep her virginity to present to her husband on the first night that further strengthens the idea of a patriarchal culture, norms and traditions of the East.Kata Kunci: representasi, signifikansi, struktur kelas, tinjauan budaya